Optimization Of 50 WP Solar Panel Power Using Heatsink Cooling And MATLAB Simulation - M. Angga Jaelani Wijaya; Suminto Suminto; Kartika Sekarsari; Agi Tama (CV. AFDIFAL MAJU BERKAH, 2026)
This research looks at the performance of a 50 WP solar panel under tropical conditions, where high temperatures often reduce its efficiency. To address this, several aluminum heatsink configurations were tested, including a 0.5 mm heatsink with a DC fan and a 6 mm zigzag design. The experiment was conducted on the rooftop of Universitas Pamulang over a period of about three months, with measurements taken between 09:00 and 15:00 WIB.The results show that the 0.5 mm heatsink can lower the panel temperature by around 10–15°C, with peak temperatures reaching approximately 42°C. Under this condition, the panel also produced the highest recorded power of 91.20 W. In comparison, the 6 mm heatsink maintained a more stable temperature range of 27–39°C, although the resulting power output was slightly lower at 82.08 W. MATLAB simulations indicate a similar pattern, suggesting improved heat dissipation and more stable thermal behavior after optimization. Overall, the use of heatsinks helps improve solar panel performance. Among the tested configurations, the 0.5 mm heatsink offers a better balance between temperature reduction and power output under the observed conditions.